Pengaruh Regulasi Diri Dan Motivasi Belajar Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Kimia Kelas X SMA Negeri 1 Lirik - Aulia Dinda Widi Andini; Copriadi, Jimmy; Herdini , Herdini (Chemistry Education Practice, 2025)
This study aims to determine the effect of self-regulation and learning motivation on Chemistry learning outcomes of class X students at SMA Negeri 1 Lirik. This research uses a quantitative approach with descriptive methods. The sample in this study amounted to 176 students who were taken through total sampling technique. The instruments used are questionnaires of self-regulation and learning motivation, as well as documentation of Chemistry learning outcomes that have been validated both theoretically and empirically. Data analysis techniques include descriptive statistics, simple linear regression tests, and multiple linear regression processed using SPSS. The results of the analysis show that self-regulation has a significant influence on Chemistry learning outcomes, although its contribution is smaller than learning motivation. Learning motivation has a more dominant positive and significant influence on students' Chemistry learning outcomes. Simultaneously, self-regulation and learning motivation together contribute 15.8% to the variation in Chemistry learning outcomes, while the remaining 84.2% is influenced by other factors outside this study. The conclusion of this study is that self-regulation and learning motivation are important factors in supporting students' academic achievement, so they need to be developed continuously through appropriate learning strategies in schools.